Trends of carbon emissions from applications of nitrogen fertiliser and crop residues to agricultural soils in South Africa. (15th October 2020) - Tongwane, Mphethe I.; Moeletsi, Mokhele E.; Tsubo, Mitsuru
Abstract: The Agriculture, Forestry and Other Land Use (AFOLU) sector produces approximately 10% of the global anthropogenic greenhouse gas (GHG) emissions and growing demands for food to meet the needs of an increasing population make it difficult to mitigate these emissions. This study investigated historical (1911–2018) nitrous oxide (N2 O) emissions from applications of synthetic nitrogen (N) fertiliser for agricultural purposes and crop residues retained in the fields post-harvest in South Africa. The aim was to develop trends of different sources of these emissions to guide national mitigation plans. Disaggregation of the emissions from key crops were developed using area planted, N application rates and residues retained in the fields. N2 O intensities were calculated to establish a relationship between agricultural emissions and socio-economic conditions. Total emissions from N and crop residues were 7.3 million tonnes (Mt) of carbon dioxide equivalent (CO2 e) emissions in 2018 and N2 O from N fertiliser was approximately 3.0 Mt. Arrival of subsidised synthetic N in the 1950s grew the emissions significantly until they peaked in the 1980s when the support was terminated. N2 O emissions per capita are gradually decreasing with time which indicates an unsustainable situation of population growing faster than its ability to produce food for itself. Less emissions per kilocalorie further indicate that crop emissions are not carbon intensive. Highlights: Policies and climate variability can influence emissions. Crop residues retained in the fields are main sources of crop emissions. Increased yields enhance emissions from crop residues. Population growth is faster than rate of food production in South Africa. Mitigating agricultural emissions needs strong policy on population growth.